2020
DOI: 10.1038/s41598-020-60728-6
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of medulloblastoma with an 18F-labeled tryptophan analogue in a transgenic mouse model

Abstract: In vivo positron emission tomography (pet) imaging is a key modality to evaluate disease status of brain tumors. In recent years, tremendous efforts have been made in developing PET imaging methods for pediatric brain tumors. Carbon-11 labelled tryptophan derivatives are feasible as PET imaging probes in brain tumor patients with activation of the kynurenine pathway, but the short half-life of carbon-11 limits its application. Using a transgenic mouse model for the sonic hedgehog (Shh) subgroup of medulloblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…The brain and heart-to-muscle ratios were significantly higher for FDG than L-[ 18 F]FETrp (n = 4, p < 0.05). The results are consistent with a high non-specific FDG uptake in the brain and heart [23]. Comparable results were observed in the liver-to-muscle ratio between the two radiotracers (Figure 3).…”
Section: Micropet Imagingsupporting
confidence: 87%
“…The brain and heart-to-muscle ratios were significantly higher for FDG than L-[ 18 F]FETrp (n = 4, p < 0.05). The results are consistent with a high non-specific FDG uptake in the brain and heart [23]. Comparable results were observed in the liver-to-muscle ratio between the two radiotracers (Figure 3).…”
Section: Micropet Imagingsupporting
confidence: 87%
“…In amino acids-deprived conditions, mTOR activity is inhibited, which promotes autophagy-dependent catabolism, providing energy and supporting cell survival. Radiotracing experiments demonstrated that tryptophan is greedily metabolized in MB patients ( Xin et al, 2020 ) and its depletion from the tumor microenvironment is associated with the activity of tryptophan catabolic enzyme indoleamine 2,3-dioxygenase 1 (IDO1). mTORC1 inhibition by rapamycin treatment was able to increase IDO1 expression ( Folgiero et al, 2016 ), suggesting the existence of a crosstalk between tryptophan levels and mTOR in MB, which is critical for the effectiveness of mTOR targeting approaches.…”
Section: Metabolic Reprogramming In Medulloblastomamentioning
confidence: 99%
“…The tryptophan and tyrosine uptake rates of MB over the ones in the healthy cerebellum were determined as 3.5–3.7 and 2.8, respectively [ 93 , 94 ]. Using these ratios and flux rates found in the healthy brain model [ 15 ], upper bounds of tryptophan and tyrosine uptakes were computed as 0.0074 mmol/gDW/h and 0.0028 mmol/gDW/h.…”
Section: Methodsmentioning
confidence: 99%